2006
DOI: 10.1111/j.1600-6143.2006.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Deposition of Lipid Complex Amphotericin-B (Abelcet) in Lung Transplant Recipients

Abstract: Lung transplant recipients exhibit a high incidence of invasive aspergillosis. The inhalation of lipid complex amphotericin-B (Abelcet; ABLC) offers a possible prophylactic strategy. The goals of this study were to select the optimal nebulizer delivery system for ABLC and to measure deposited aerosol dose in 12 lung transplant recipients. In vitro testing was performed to select a nebulizer delivery system, and an empirical model was used to estimate lung deposition. Estimated pulmonary doses varied by as much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 27 publications
0
50
0
1
Order By: Relevance
“…15 Corcoran et al also reported sub-optimal amphotericin B distribution in the native lung with the use of a radiolabeled lipid complex amphotericin B. 19 The cost of prophylaxis with n-LAB is higher than with conventional nebulized amphotericin B, but lower than with other drugs. The cost of our current protocol (25 mg 3 times per week up to Day 60, 25 mg once per week up to Day 180) has been estimated at 2,997 euros/patient in the first 6 months.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…15 Corcoran et al also reported sub-optimal amphotericin B distribution in the native lung with the use of a radiolabeled lipid complex amphotericin B. 19 The cost of prophylaxis with n-LAB is higher than with conventional nebulized amphotericin B, but lower than with other drugs. The cost of our current protocol (25 mg 3 times per week up to Day 60, 25 mg once per week up to Day 180) has been estimated at 2,997 euros/patient in the first 6 months.…”
Section: Discussionmentioning
confidence: 97%
“…16 Other formulations of inhaled amphotericin B (lipid complex and liposomal amphotericin) have been proposed for prophylactic purposes, with promising results. [17][18][19][20] In some experimental models, nebulized liposomal amphotericin B (n-LAB) has been shown to be more effective 21 and long-lasting 22 than the conventional formulation.…”
mentioning
confidence: 99%
“…All three formulations were shown to be safe and well tolerated. Patients receiving amphotericin B lipid complex, however, had fewer side effects [60]. Administration of inhaled amphotericin also results in lack of systemic antifungal effects, resulting in 12-14% of systemic fungal infection within 2 months of initiating the prophylaxis [59].…”
Section: Antifungal Prophylaxis In Lung Transplant Recipientsmentioning
confidence: 99%
“…In Fig. 2b, a standard model [14] is applied to predict what portion of the total test aerosol volume would deposit within different portions of the lung if it were inhaled. Approximately 41% of the test aerosol would deposit in the lungs if inhaled with 28% depositing within the deep lung (alveoli).…”
Section: Test Aerosolmentioning
confidence: 99%